Redefining the association between old age and poor outcomes after trauma: The impact of frailty syndrome. Issue 3 (March 2017) - Joseph, Bellal; Orouji Jokar, Tahereh; Hassan, Ahmed; Azim, Asad; Mohler, Martha Jane; Kulvatunyou, Narong; Siddiqi, Shirin; Phelan, Herb; Fain, Mindy; Rhee, Peter
Abstract : BACKGROUND: Frailty syndrome (FS) is a well-established predictor of outcomes in geriatric patients. The aim of this study was to quantify the prevalence of FS in geriatric trauma patients and to determine its association with trauma readmissions, repeat falls, and mortality at 6 months. METHODS: we performed a 2-year (2012–2013) prospective cohort analysis of all consecutive geriatric (age, ≥ 65 years) trauma patients. FS was assessed using a Trauma-Specific Frailty Index (TSFI). Patients were stratified into: nonfrail, TSFI ⩽ 0.12; prefrail, TSFI = 0.1 to 0.27; and frail, TSFI > 0.27. Patient follow-up occurred at 6 months to assess outcomes. Regression analysis was performed to assess independent associations between TSFI and outcomes. RESULTS: Three hundred fifty patients were enrolled. Frail patients were more likely to develop in-hospital complications (nonfrail, 12%; prefrail, 17.4%; and frail, 33.4%; p = 0.02) and an adverse discharge disposition compared with nonfrail and prefrail (nonfrail, 8%; prefrail, 18%; and frail, 47%; p = 0.001). Six-month follow-up was recorded in 80% of the patients. Compared with nonfrail patients, frail patients were more likely to have had a trauma-related readmission (odds ratio [OR], 1.4; 95% confidence interval [CI], 1.2–3.6) and/or repeated falls (OR, 1.6; 95%CI, 1.1–2.5) over the 6-month period. Overall 6-month mortality was 2.8% (n = 10), and frail elderly patients were more likely to have died (OR, 1.1; 95% CI, 1.04–4.7) compared with nonfrail patients. CONCLUSION: Over a third of geriatric trauma patients had FS. TSFI provides a practical and accurate assessment tool for identifying elderly trauma patients who are at increased risk of both short-term and long-term outcomes. Early focused intervention in frail geriatric patients is warranted to improve long-term outcomes. LEVEL OF EVIDENCE: Prognostic study, level II. Abstract : Supplemental digital content is available in the text.